Internalizing externalities through public pressure: Transparency regulation for fracking, drilling activity and water quality - Pietro Bonetti; Christian Leuz; Giovanna Michelon (Goethe University Frankfurt, Center for Financial Studies (CFS), 2024)
The rise of shale gas and tight oil development has triggered a major debate about hydraulic fracturing (HF). In an effort to bring light to HF practices and their potential risks to water quality, many U.S. states have mandated disclosure for HF wells and the fluids used. We employ this setting to study whether targeting corporate activities that have dispersed externalities with transparency reduces their environmental impact. Examining salt concentrations that are considered signatures for HF impact, we find significant and lasting improvements in surface water quality between 9-14% after the mandates. Most of the improvement comes from the intensive margin. We document that operators pollute less per unit of production, cause fewer spills of HF fluids and wastewater and use fewer hazardous chemicals. Turning to how transparency regulation works, we show that it increases public pressure and enables social movements, which facilitates internalization.
Keywords: D62; G38; K22; K32; L71; L72; M41; M48; Q53; 330; Environmental regulation; Fracking; Real effects; Disclosure; Water pollution; Sustainability; Corporate social responsibility; Externalities; Unconventional oil & gas development